Molecular and serological detection of Trypanosoma cruzi in dogs (Canis lupus familiaris) suggests potential transmission risk in areas of recent acute Chagas disease outbreaks in Colombia (2017)
Chagas disease is a zoonotic infection widely distributed in tropical and subtropical regions of America, including more than 50% of the Colombian territory. In the last years, an increase of outbreaks of acute Chagas disease has been observed in the east of the country due to environmental changes and mammal movements toward human settlements. Given the importance of dogs (Canis lupus familiaris) as reservoir hosts and sentinels of Trypanosoma cruzi infection across different regions of America, in this study we reported a serological and molecular detection of T. cruzi infection in 242 dogs from an endemic area of Meta department (East of Colombia), with recent emergence of acute Chagas disease outbreaks. The distribution of T. cruzi infection in dogs was not homogeneous, ranging from 0–41.4% and 0–5.1% in different sampling sectors, through serological (ELISA/IFAT) and molecular methods (conventional and real time PCR), respectively. Statistical analysis indicated that dog infection was associated with specific sampling sectors. Our results show a moderate seroprevalence of infection and active circulation of T. cruzi in dogs from this zone, which suggest areas with potential risk of infection to human that must be taken into consideration when Chagas disease control programs need to be implemented. © 2017 Elsevier B.V.